ANALISIS BEBAN KERJA MENTAL PESERTA MAGANG PADA HOTEL XYZ JAKARTA - Lintang Ratri Maharani; Adetiya Prananda Putra; Eka Afrida Ermawati; Jemi Cahya Adiwijaya; Ahmadintya Anggit Hanggraito (Politeknik Bosowa, 2026)
This study aims to analyze the level of mental workload experienced by interns at Hotel XYZ Jakarta Indonesia, a five star hotel that regularly hosts internship programs each year. The research employs a descriptive quantitative approach using the NASA-TLX (National Aeronautics and Space Administration Task Load Index) method to subjectively measure mental workload. Data were collected through observation, questionnaires, and document analysis involving the 2024 Batch 2 interns. The results reveal that the majority of interns experience a high level of mental workload, with 47% classified in the high category and 30.3% in the very high category indicating that approximately 77% of interns face significant work pressure. The most dominant workload indicators were Performance, Physical Demand, and Mental Demand. The highest levels of workload were found in the F&B Kitchen, Housekeeping, and F&B Service departments. However, departments with fewer interns such as Finance, Sales & Marketing, and Talent & Culture also reported notable levels of mental pressure. Overall, operational departments tend to experience higher physical and time-related workloads, while non-operational departments face greater mental pressure. This reflects the differing characteristics between front-of-house and back-of-house roles.